Application of Think-Pair-Share (TPS) Cooperative Learning Model to Student Learning Outcomes in Hydrocarbon Material in Senior High School - Kifli, Moh.; Mustapa, Kasmudin; Ratman, Ratman (Jurnal Akademika Kimia, 2023)
This study aims to describe the improvement of student learning outcomes by applying the Think-Pair-Share (TPS) cooperative learning model on hydrocarbon material in class XI SMA Negeri 2 Sigi. This study's research type is pre-experimental with a one-group pretest posttest design. This study utilized purposive sampling. The sample consisted of two classes: class XI IPA 3 as the experimental class 1 (n = 22) and class XI IPA 4 as the experimental class 2 (n = 24). Student learning outcomes data are processed using the learning improvement test (N-gain). The application of the Think Pair Share (TPS) cooperative learning model to improve student learning outcomes on Hydrocarbons can be seen from the average N-gain value in the two experimental classes, including in the high category, namely 0.77 and 0.78. Therefore, applying the Think Pair Share (TPS) cooperative learning model can improve student learning outcomes on average greater than 75 (KKM) of SMA Negeri 2 Sigi students in Class XI on hydrocarbon material.